LANGUAGE STYLE OF BEAUTY PRODUCT IN COMMERCIAL ADVERTISEMENT DISPLAYED ON JAPANESE TELEVISION - Supriatnadi, Nandi; Hasibuan, Adriana; Pawiro, Muhammad Ali (Universitas Islam Sumatera Utara (UISU), 2023)
This study examines the diction and style of language in commercial advertisements for Nivea beauty products and aims to describe and explore the meanings of the expressions written in the advertisements. Data in the form of phrases, sentences, and images are analyzed using a qualitative descriptive analysis. The results of the study show that the dictions in the Nivea-UV (予防美容ケア) advertisements are all directly related to the vocabulary for beauty care. There are also borrowed words from English to clarify the products offered. The style of language in the advertisement consists of eight hyperboles, two metaphors, and one synecdoche, metonymy, repetition, and onomatopoeia, respectively. The style appears in the form of exaggeration, presenting something clearly, repeating words, emphasizing certain words, showing the same word order, having words that express a relationship, and having words that represent associations or attributes. To refine language, there is politeness in the language forms of kenjou and teinei. The diction and style of language have their own characteristics, namely firmness and solidity, so that the intentions and meaning of the advertisement can be understood by the target audience.